Electrochemical properties of roots determine antibiotic adsorption on roots - Liu, Yuan; Tao, Zhen; Lu, Hailong; Li, Siyi; Hu, Chao; Li, Zhongyang (Frontiers in Plant Science, 2023)
The adsorption behaviors and transfer pathways of antibiotics in plant-soil system are greatly influenced by the electrochemical properties of both soil particles and plant roots. However, the effects of roots electrochemical properties on antibiotics adsorption are largely unknown. Here, the fresh soybean, maize and wheat roots with different electrochemical properties were obtained from hydroponic cultivation, and the adsorption processes and mechanisms of doxycycline, tetracycline, sulfadiazine and norfloxacin on roots under various environmental conditions were investigated. Results showed that the adsorption amount of antibiotics on roots increased with the initial concentration of antibiotics. The coexisting low molecular organic acids and anions inhibited the antibiotic adsorption on roots. The soybean roots performed strong adsorption ability compared to the maize and wheat roots driven by the variations in root electrochemical properties. This study demonstrates the significances of electrochemical interactions between antibiotics and roots in plant-soil system and can contribute to the more accurate risk assessment and effective pollution control of antibiotics.